Theorizing Competition. An interdisciplinary approach to the genesis of a contested concept - Stephan Pühringer; Georg Wolfmayr; Carina Altreiter; Claudius Gräbner; Ana Rogojanu (Johannes Kepler University Linz, Research Project SPACE - Spatial Competition and Economic Policies, 2020)
Competition is at the core of economics, being both a central concept of economic reasoning and a main prerequisite for economic action. Yet, the attempt of a clear definition of competition is challenging as the concept of competition has been used in different historical and disciplinary contexts. This paper provides an analytical and historical comparison between conceptions of competition from economics, sociology and anthropology. Our interdisciplinary review and systematisation show how different conceptions of competition are bound up with different ways to theorize the relation between an "economic realm" and a "social realm". By focusing on the scope and normative implications of these concepts, we aim to develop a better understanding of competitization, i.e. the expansion of competitive modes of regulation and practices.
Keywords: 330; competition; interdisciplinarity; competitization; 'economic' and 'social' realm